Understanding the role of emotion and expertise in psychotherapy: An application of dynamical systems mathematical modeling to an entire course of therapy - Diaz, Patricia; Peluso, Paul R.; Freund, Robert; Baker, Andrew Z.; Peña, Gabriel (Frontiers in Psychiatry, 2023)
The therapeutic relationship is one of the most important factors in creating change in psychotherapy. This study used a validated observational coding system--the Specific Affect Coding System (SPAFF) and a theoretical mathematical model to analyze behaviors which make up the therapeutic relationship over the course of six sessions. Dynamical systems (DS) mathematical modeling was also employed to depict the relational dynamics between the master therapist and his client over six sessions. Statistical analysis was used to compare SPAFF codes and model parameters between the expert therapist and his client. The expert therapist showed stability in affect codes over six sessions while the client’s affect codes appeared to be more flexible over time. In addition, DS model parameters remained stable across the six sessions for both client and therapist. Finally, phase space portraits depicted the evolution of the affective dynamics between the master therapist and his client as the relationship matured. These results provide a valuable foundation for future research on emotional expression as a key component of the therapeutic relationship in psychotherapy.